A novel exercise testing algorithm to diagnose mitochondrial myopathy - Bhatia, Rajeev; Cohen, Bruce H.; McNinch, Neil (Muscle & nerve, 2021)
Introduction Oxygen uptake efficiency slope (OUES) is a noninvasive cardiopulmonary exercise testing (CPET) measurement based on oxygen uptake (V˙O2) and minute ventilation (V˙E) and is a marker of the efficiency of oxygen utilization by the body. However, it has not been studied in mitochondrial disorders. We explored noninvasive CPET parameters, including OUES, as a way to reliably diagnose mitochondrial myopathy. Methods We performed cycle ergometer maximal exercise testing on definite and suspected mitochondrial myopathy subjects (MM‐D and MM‐S) and their age‐ and sex‐matched controls. OUES was corrected for body surface area (OUES/BSA) to eliminate the effect of body size. Results A total of 40 participants, including 20 MM‐D (n = 13; 6 males; aged 14‐64 years) and 7 MM‐S (5 males, aged 11‐30 years) subjects and 20 controls, completed the study. MM‐D subjects showed lower aerobic fitness than controls. OUES/BSA was lower in MM‐D subjects, suggesting inefficient oxygen utilization. Area under the curve (AUC) and 95% confidence interval (CI) for OUES/BSA (AUC, 0.91; 95% CI, 0.80‐1.00), peak V˙O2 percent predicted (AUC, 0.95; 95% CI, 0.86‐1.00), and V˙O2/work slope (AUC, 0.94; 95% CI, 0.85‐1.00) showed excellent ability to diagnose mitochondrial myopathy in MM‐D subjects. We applied a diagnostic approach based on the parameters just noted to MM‐S subjects and their controls and were able to support or disprove the diagnosis of mitochondrial myopathy. Discussion We proposed and applied an approach based on the aformentioned three CPET parameters to diagnose mitochondrial myopathy reliably and found it to be clinically useful.